Microbial characterization of a natural biofilm associated with peruvian scallop (Argopecten purpuratus) larvae settlement on artificial collector by confocal imaging, microbiology, and metagenomic analysis - González-Pazmiño J. (2021)
Biofilms strongly influence bivalve settlement patterns on artificial substrates; however, their structure and taxonomic composition remains a black box. We characterized a natural biofilm composition that exhibits a large settlement of larvae of the Peruvian scallop Argopecten purpuratus by culture-dependent and culture-independent methods. Thirty-two different strains, representing six genera (10 strains of Bacillus, 9 of Vibrio, 6 Acinetobacter, 4 Staphylococcus, 2 Photobacterium, and 1 Exiguobacterium) were isolated. Those strains represented only 1.09% of the relative abundance compared with the total microbiota obtained by 16S rRNA high-throughput sequencing. The metagenomic analysis identified 441 species. Prokaryotes were predominant (93.4%) over eukaryotes (6.6%), with Pelobacter (13.4%), Lewinella (5.6%), Marinobacter (5.4%), Hoeflea (4.2%), and Microcystis (3.1%) being the most representative genera. Laser scanning confocal microscopy (LSCM) imaging evidenced an irregular and heterogeneous biofilm with an average thickness of 35 µm, where the heterotrophic prokaryotic community (3.4×106 cell cm-2) dominate the photoautotrophic communities (2.3×105 cell cm-2). For the first time, an A. purpuratus settlement-related biofilm was described by the next generation sequencing tool (NGS) and compared with traditional methodologies.